Existential semiotic analysis of the temporal and subjective dimensions of art music performance - Macdonel, Grisell (Interdisciplinary Studies in Musicology, 2018)
For the philosophers, aesthetics and musicologists of the nineteenth and twentieth centuries the topic of subjectivity in art music was a controversial issue. According to them the musical art work had to be objective. However since the subjectivity of the performer has an important influence on aspects such as sound, rhythm, tempo and emotional input, her presence was considered an obstacle for achieving objective musical works. Most of the theoretic approaches to art music supported such an idea and showed a negative perspective on performance and, even though few scholars argued about the value of performance, the main trend pointed at the performer’s subjectivity as an endangerment of music as an objective art. This article conceives art music as a sonic and temporal phenomenon and, from this perspective considers that the performer’s subjectivity is an important and active element that plays a key role in the creation of musical art works. From an existential semiotic perspective this article analyses distinct aspects of the performer’s subjectivity and develops an adaptation of this theory created by Eero Tarasti to the study of subjectivity in performance and its relation with temporality. The existential semiotic theory claims that signs are created by subjects in their act of existing. In this manner subjectivity is located as a central element deeply involved in semiosis processes that creates a rich universe of signs and meaning. This article attempts to show that the sonic dimension of art music can be enriched by the presence of the performer’s subjectivity rather than being an endangerment for it.